Surgical management of intracranial aneurysms in the “coiling age” - Júnior, Francisco Ramos; Pinheiro Marques, João Antônio; de Albuquerque, Lucas Alverne Freitas; Paiva Santos, Flávia de; de Almeida, João Paulo Cavalcante; de Lucena, João Mairton Pereira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2009)
Background: Intracranial aneurysm rupture is associated with substantial rates of morbidity and mortality. The classic neurosurgical treatment for such lesions is the craniotomy for clipping. However, over the last 10 years, surgery has been increasingly replaced by the endovascular technique. Objective: Analyze the results of surgery technique in a Public Health Hospital in the “coiling age”. Method: We reviewed a series of 149 patients treated for 191 aneurysms by the traditional craniotomy and clipping technique. Results: We observed an overall mortality of 12.1%, poor outcome of 8% and good outcome of 79.8%. Hunt Hess scores ≥ 3 in the pre-surgical evaluation were associated to a higher length of hospital stay (p = 0.047). Better outcome was observed in patients with Hunt Hess score < 3 comparing with patients with Hunt Hess score ≥ 3 before surgery (p < 0.000). Patients who presented with Fisher Scale grade 4 presented a poor prognosis when compared to the other groups (p = 0.016). Conclusion: Excellent results may be achieved by craniotomy to treat aneurysms, which still represents a useful technique for lesions that can not be safely treated by endovascular techniques nowadays.
Keywords: Cerebral aneurysm, surgical treatment